Analisis Kemampuan Bersosialisasi Anak Usia Dini di Paud Seroja 1B Cikarang Barat - Putri Indah Dwi Yuliastari; Ddang Danugiri; Ika Rizqi Melya (Peneliti.net, 2022)
Knowing how the social skills of children and the efforts of the role of educators in improving social skills in PAUD Seroja 1B Cikarang. This type of research is a descriptive qualitative research field used, namely research conducted in real life. While the type of analysis used is qualitative (qualitative research), namely research that aims to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of people individually or in groups. The social skills of children in PAUD Seroja 1B Cikarang are quite good because children can be independent in the classroom. The role of educators in improving children's social skills at PAUD Seroja 1B Cikarang is to be able to respond to feelings and give praise to children, show empathy, and be able to motivate children. Teachers also exemplify the nature of discipline to children, such as arriving on time. (a) Teachers must familiarize children with the culture of queuing in any case. (b) Teachers should make games or role plays for children's emotional games. (c) As a parent, you must pay attention to your child's social skills by giving the child the freedom to play outside but still under parental supervision. (d) For further research, it is hoped that this research can be used as a reference and can be developed more widely. (e) Future researchers are also expected to use different variables from this research.